ABDURAUF FITRAT AND HIS CONTRIBUTION TO LANGUAGE TEACHING. (Ustozlar uchun, 2026)
This article examines the contribution of Abdurauf Fitrat to the development of language teaching and national education in Uzbekistan. Special attention is given to his educational ideas, linguistic views, and reformative activities during the Jadid movement. The study highlights Fitrat’s efforts to modernize teaching methods, simplify literary language, and promote cultural awareness through education. His works played a significant role in the formation of modern Uzbek language teaching principles and continue to influence contemporary pedagogy and linguistics.